Influence of Brushing Time on Food Dynamics and Commercial Traits of Bombyx mori L. in Sub-tropical Plains of Jammu Region - Sajgotra, Mokshe; Bali, R. K. (International Journal of Bio-resource and Stress Management, 2017)
In the present investigation, an attempt was made to study the effect of brushing time, silkworm hybrids and mulberry varieties for food dynamics and commercial trait expression. The experiment was laid out in factorial-completely randomized block design with eight treatments and three replications and the analysis of treatments was worked out by analysis of variance technique. The treatments comprised of two brushing time (early i.e. 1st of March and late i.e. 20th of March), two hybrids (PO3×ND5 and SH6×NB4D2) and two mulberry varieties (China white and Tr-10). The brushing time, silkworm hybrids and mulberry varieties influenced significantly most of the food dynamic and cocoon traits. Observations made for food dynamics and commercially important traits indicated that, food ingestion and digestion, conversion of ingested and digested food, approximate digestibility, production efficiency of cocoon shell, efficiency of cocoon production, percentage of cocoon shell weight, effective rate of rearing (by weight and by number), single cocoon weight, single shell weight, shell ratio percentage, fibroin and sericin content, total filament length, non-breakable filament length and renditta were significantly higher for early brushing time, PO3×ND5 and China white. Thus, only one commercial rearing is possible with brushing time of early i.e. 1st of March for hybrid PO3×ND5 fed on China white mulberry variety for spring rearing in the field at farmer’s level for better prospects of bivoltine sericulture in sub-tropical plains.